'Dismantle, change, build': Designing abolition at the intersections of local, large-scale, and imagined infrastructures. (November 2018) - Agid, Shana
Abstract : As a theory and practice within the field of participatory design, infrastructuring holds complex intersections between people, groups, technologies, systems, and ideologies in view. Building on other researchers in participatory design, this article argues for an approach to infrastructuring that focuses on how we do, and create capacity to do, the work of infrastructuring locally with people and groups affected by and working in relation to the systems we seek to engage. These dynamics are explored in the literature and through a case story of an embedded design engagement with a social justice organization, where our focus and the relational practices we designed through long-term work together were shaped by the intersections of local, large-scale, and imagined infrastructures central to their organizing work. Highlights: Studies an embedded design engagement to explore local infrastructuring Proposes "designing relational practice" as an approach to long-term PD work. Proposes design at intersections of local, large-scale, & imagined infrastructures. Advocates a (re)turn to analyses of infrastructuring as local, embedded practices. Advocates an understanding of infrastructures as visible in their harmful effects.